Improvement of Student Physics Learning Outcomes through Peer Tutor Learning Model of SMA 3 Bengkalis - Suryani Suryani (Universitas Riau, 2019)
This research was a classroom action research using a peer tutor learning model to improve physics learning outcomes. Peer tutor learning is a learning that utilizes classmates who have more ability to help their friends in carrying out an activity or understanding the concept of learning. The problem to be solved is the low physics learning outcomes of class XI IPA 3 in SMA 3 Bengkalis. This study consisted of three cycles, in each cycle consisting of four stages, namely Planning, Implementation, Observation and Reflection. This research involved 21 students which are consisting of 13 female students and 8 male students. In the pre-cycle process, the percentage of learning completeness was 19.05%, then after learning the first cycle using the peer tutoring model there was an increase in the percentage of learning completeness to 42.89%. In the second cycle, it increased again to 61.91% and in the third cycle, it succeeded in achieving the percentage of learning completeness of 85.71%. The results showed that an increase in student learning outcomes along with the application of peer tutoring models. Thus, the results of the study indicate that the use of peer tutoring models can improve the physics learning outcomes of XI IPA 3 students in SMA 3 Bengkalis.